Semantic Exploration of the Word 'Imra'ah' in the Qur'an: Differences in Meaning and Forms - Muhammad, Adamu Abubakar; Alrumayh, Safa; Hidayat, Ahmad Fadhel Syakir; Touré, Youcha Alassane; Riaz, Shehla (Borneo Journal of Language and Education, 2026)
One of the key issues in Qur'anic linguistic studies is lexical ambiguity, where a single word may convey multiple meanings depending on its form and context. The word “imra’ah” appears in various forms in the Qur'an and demonstrates semantic variation that cannot be fully understood through general or dictionary-based interpretation alone. Despite its frequent occurrence, this term has not been sufficiently analyzed from an integrated semantic and morphological perspective. This study aims to: (1) identify the meanings of the word “imra’ah” in the Qur'an, and (2) analyze its morphological forms. This research employs a qualitative library approach, with data collected from Qur'anic verses, dictionaries, and tafsir sources. The analysis is conducted by identifying occurrences of “imra’ah”, classifying them based on their forms, and interpreting their meanings within context, supported by linguistic and exegetical comparisons. The findings show the word “Imra’ah” in the Qur'an has two meanings: (1) woman, and (2) wife, with two forms: (1) with or without idhafah, and (2) with ta' marbuthah or ta' maftuhah. The word “Imra’ah” with idhafah, whether attached to a pronoun or a noun, refers to the meaning of wife, while without idhafah or in its dual form, it means woman. In its singular form, the word “Imra’ah” with ta’ marbuthah means woman, while with ta’ maftuhah it means wife. These findings have practical implications for Qur'anic interpretation and Arabic language learning, helping to avoid misinterpretation and providing a clearer understanding of the relationship between form and meaning.